Achieving Efficient n‑Doping of Conjugated Polymers by Molecular Dopants - Lu, Yang; Wang, Jie-Yu; Pei, Jian (Accounts of chemical research, 2021)
Conspectus Molecular doping is one of the most central propositions in the field of organic electronics. Unlike classical inorganic semiconductors doped by atomic substitution, organic conjugated materials react with molecular dopants, and then intermolecular charge transfer is involved within. Therefore, the complex noncovalent interactions between two components often cause the molecular dopant to destroy the orderly stacking of the host organic materials and reduce the original properties of the material, such as carrier mobility, which here we call the “doping dilemma.” Recently, many studies focus on improving p-doping efficiency and electrical conductivity of doped conjugated polymers; however, the development of n-type molecular doping currently lags far behind that of its p-counterpart. It is well-known that both efficient p- and n-type molecular doping are indispensable in various organic electronic devices, including light-emitting diodes, photovoltaics, field-effect transistors, and thermoelectrics. It is thus an urgent requirement to achieve efficient n-doping in conjugated polymers. In this Account, we give a brief overview of our efforts to improve the n-doping efficiency in conjugated polymers with several strategies from the aspects of the polymer/dopant molecular design and the exploration of the n-type molecular doping mechanism and charge transport mechanism in n-doped organic materials. For the conjugated polymer engineering, we first demonstrate that increasing the electron affinity of the host polymer through halogen substitution can boost the n-doping efficiency. Still, the rigid coplanar backbones of conjugated polymers play a crucial role in the polaron delocalization and final electrical performance. In addition, we emphasize the importance of morphology control in the doped polymers to address the “doping dilemma.” For n-dopants designing, we summarize some basic guidelines from molecular sizes and shapes, the interaction between dopants (or dopant cations) and polymers, and the effects of dopants on morphology to design high-efficacy n-type molecular dopants. We propose that the polymers and the dopants need to be treated as a whole system; while enhancing the ionization efficiency, more attention should be paid to the carrierization (free-carrier generation) efficiency of these binary systems. In the end, we adopt the n-type polymer thermoelectric material as an example to discuss the grand challenges encountered in practical applications of n-doped conjugated polymers. The air stability and micrometer-thick thermo-leg processing of n-doped polymers are highlighted for thermoelectric applications. It is our hope that this Account showcases a blueprint for rational approaches and a deep understanding toward the design and development of efficient n-doping in conjugated polymers, bringing n-doped organic materials into the next era.